2021
DOI: 10.47815/apsr.2021.10029
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lime, phosphorus and boron on performance of maize (Zea mays L.)in acidic soil of Nagaland

Abstract: A pot experiment was conducted in an acidic sandy clay loam soil during the kharif season of 2016 and 2017 to study the performance of maize using two lime levels (0 and ¼ lime of LR), four phosphorus levels (0, 13.4, 26.8 and 40.2 mg P2O5 kg-1) and three boron levels (0, 0.45 and 0.90 mg B kg-1) with maize as test crop. The experiment was designed in complete randomized design with three replications. Results revealed that plant height, number of leaves and leaf area index increased appreciably with the advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…This result is in agreement with the findings of [38]. Application of K can lead to increased metabolic activities and better root proliferation in legumes ultimately resulting in enhanced seed setting and pod formation [39]. These findings are in conformity with study reported by Hussain et al [40][41][42].…”
Section: Seed Yieldsupporting
confidence: 93%
“…This result is in agreement with the findings of [38]. Application of K can lead to increased metabolic activities and better root proliferation in legumes ultimately resulting in enhanced seed setting and pod formation [39]. These findings are in conformity with study reported by Hussain et al [40][41][42].…”
Section: Seed Yieldsupporting
confidence: 93%
“…The presence of the rhizobium makes the soil fix the atmospheric nitrogen for the availability of nitrogen to the plant which helps in plant growth in a healthier way and increases the yield parameters like Pods/plant, seeds/pod and pod length. Similar, observations were reported by Priyanka Sharma and Prakash Borah, (2020) [24] , Nusakho Nyekha et al, (2015) [14] , P Vinodhini et al, (2022) [16] , F. K. Mbaka et al, (2022) [5] , Yubaraj Dhakal et al, (2016) [26] , B Bhabai et al, (2019) [6] . Grain yield: The treatment T7 (NPK Foliar 12:32:16 + Rhizobium) produced the maximum grain yield among all the other treatments and statistically at par with T8 (NPK Foliar 12:32:16 + VAM).…”
Section: Yield Parameters Pods/plant Seeds/ Pod and Pod Lengthsupporting
confidence: 77%
“…On most acid soils, there are several limiting factors for plant growth, including toxic levels of Al, Mn, and iron (Fe), as well as deficiencies of some essential elements, such as phosphorus (P), nitrogen (N), potassium (K), calcium (Ca), Mg, and some micronutrients such as Mo and B [2], low microbial activity, poor fertility, and low crop yields. To meet the demands of calcium and magnesium, as well as to create favorable conditions for better uptake of other essential nutrients, liming is an important management practice in the acid soils helping in raising the pH and base saturation of the soil and inactivation of iron, aluminium and manganese in the soil solution and minimizing phosphate fixation by iron [3,4,5].…”
Section: Introductionmentioning
confidence: 99%